YouTube and the Role of Digital Video for Transitional Justice in Syria - Wessels, Joshka Ivanka (Politik, 2016)
International media access is extremely limited in Syria and many human rights organisations rely on individual citizens and activists to provide them with evidence that could indicate war crimes and crimes against humanity. The role of YouTube and digital video for transitional justice in Syria is the central theme of this research paper. Research methodology is based on systematic observation of video clips on YouTube, visits to Syrian grass root audio-visual media centres and semi-structured interviews with Syrian video activists on the ground in Turkey and Syria. Fort this study, a conceptual thematic categorisation of eight different video-categories has been developed, based on observation, media-ethnography and regular monitoring of clips coming out of Syria since 2011 and in-depth surveillance of YouTube material uploaded between 2014 and 2015. In total 400 YouTube video clips were surveyed, analysed and monitored between 2014 and 2015. The paper assesses the feasibility of using these clips for legal evidence of war crimes and crimes against humanity. The paper considers the latest approaches to using and verifying digital audio-visual material and how video can be used for future transitional justice and conflict resolution.